Análise do desempenho de refrigeradores termoacústicos - Nascimento, Andreia Aoyagui (2011)
The research interest on refrigeration systems has increased in the last years as indicated by the great number of scientific publications in the last years. The research on thermoacoustic refrigerator and its application has been significant, justified by the technological, economic and enviromental advantages of these devices when compared with conventional refrigeration systems. So the study of the thermoacoustic phenomenon is fundamental to understand the behavior and the application of these refrigeration systems. This work presents a study of the thermoacoustic effect inside an open duct using air as the working fluid. The thermoacoustic analytical model is developed to obtain the equations that represent the thermoacoustic effect. The software DeltaEC is used to calculate the steady state behavior of the system. Finite element models with refined geometry are also formulated. The software Ansys ® is used to calculate the natural frequencies, the vibration modes, and the harmonic response of the refrigerator. The software Ansys CFX ® is used to analyse transient behavior of the system. In order to validate the computational models, their results are compared with those obtained from a refrigerator experimental device, which allowed satisfactory results about DeltaEc and Ansys®, and the CFX limitation to reproduce this phenomenon.